2000
DOI: 10.1046/j.1460-9568.2000.00069.x
|View full text |Cite
|
Sign up to set email alerts
|

The ginkgo biloba extract (EGb 761) protects hippocampal neurons against cell death induced by β‐amyloid

Abstract: Substantial evidence suggests that the accumulation of beta-amyloid (Abeta)-derived peptides, and to a lesser extent free radicals, may contribute to the aetiology and/or progression of Alzheimer's disease (AD). Ginkgo biloba extract (EGb 761) is a well-defined plant extract containing two major groups of constituents, i.e. flavonoids and terpenoids. It is viewed as a polyvalent agent with a possible therapeutic use in the treatment of neurodegenerative diseases of multifactorial origin, e.g. AD. We have inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
243
2
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 354 publications
(257 citation statements)
references
References 58 publications
10
243
2
2
Order By: Relevance
“…A CMV␤Gal plasmid (Clontech, Mountain View, CA) was included as a control to normalize variations among transfections. Transfected cells were then cultured for 2 days in the presence of EGb 761 at 0 to 200 g/ml, or its purified components terpene bilobalide and ginkgolide B at equivalent composition percentages (Ipsen Laboratories, Paris, France), 20,21 and harvested for the luciferase reporter gene assay using a luciferase assay system (Promega, Madison, WI). EGb 761 is extracted from green leaves of the Ginkgo biloba tree to a formulation of 24% flavonoids, 6% terpenes (eg, ginkgolides and bilobalide), 5 to 10% organic acids, and Ͻ0.5% proanthocyanidins.…”
Section: Cell Cultures Transfection Egb 761 Treatment and Reportermentioning
confidence: 99%
See 1 more Smart Citation
“…A CMV␤Gal plasmid (Clontech, Mountain View, CA) was included as a control to normalize variations among transfections. Transfected cells were then cultured for 2 days in the presence of EGb 761 at 0 to 200 g/ml, or its purified components terpene bilobalide and ginkgolide B at equivalent composition percentages (Ipsen Laboratories, Paris, France), 20,21 and harvested for the luciferase reporter gene assay using a luciferase assay system (Promega, Madison, WI). EGb 761 is extracted from green leaves of the Ginkgo biloba tree to a formulation of 24% flavonoids, 6% terpenes (eg, ginkgolides and bilobalide), 5 to 10% organic acids, and Ͻ0.5% proanthocyanidins.…”
Section: Cell Cultures Transfection Egb 761 Treatment and Reportermentioning
confidence: 99%
“…17 To investigate whether EGb 761 would have neuroprotective effects on these Tat-induced phenotypes, we first injected mice intraperitoneally with Dox for 7 days and then orally administrated EGb 761 for an additional 21 days at a dosage of 100 mg/kg/day. 21,27 There were seven age-matched mice in each of four experimental groups ( Figure 1, A and B). Mouse survival and growth were monitored on a daily basis.…”
Section: Egb 761 Improves Development and Survival Of Tat Transgenic mentioning
confidence: 99%
“…However, the actions of flavonoids are complex and often seemingly antagonistic or paradoxical. For example, while flavonoids are described as antioxidant agents protecting against oxidative insults to cells and apoptosis [11,13,88], others have found flavonoids to be pro-oxidants and -apoptotic [33,212,221]. Thus, it becomes clear that the effects of flavonoids depend on different factors such as the specific compound used, the cell type, concentrations, experimental design, and the general context in which flavonoids are used.…”
Section: Biological and Cellular Propertiesmentioning
confidence: 99%
“…Other authors reported beneficial effects of G. biloba extract against beta-amyloid-mediated neurotoxicity in primary hippocampal neurons [11,57] and implicated antioxidant activities and the modulation of intracellular calcium levels in PC12 cells [209] as possible mechanisms of action. Other lines of research focused on the binding of flavonoids such as apigenin, naringenin, kaempferol, quercetin-3-O-glucoside and others to benzodiazepine binding sites [149] of different receptors including the GABA-A-receptor [52,132] and adenosine receptors [139], and investigated their anxiolytic potential [149] as a possible mechanism of action in the CNS.…”
Section: Flavonoids: Neuroprotective Agents In Vivo and In Vitro?mentioning
confidence: 99%
“…Both EGb-761 and its constituents have been investigated for their neuroprotective properties against Ab-induced toxicity. Treatment with EGb-761 and its flavonoid fraction CP205 rescues N2a, PC-12, and primary mixed hippocampal cell cultures from Ab-stimulated apoptosis by counteracting elevations in reactive oxygen species, and preventing NF-kB activation [Bastianetto et al, 2000;Longpre et al, 2006;Yao et al, 2001]. Such anti-inflammatory and antioxidative properties might account in part for the protective effects of ginkgolides A, B, and J in reducing Ab 42 -induced decreases in synaptophysin levels and restoring long-term potentiation in hippocampal slice cultures [Bate et al, 2008;Vitolo et al, 2007].…”
Section: Gingko Bilobamentioning
confidence: 99%